Material properties of biomolecular condensates emerge from nanoscale dynamics - Nicola Galvanetto; Miloš T. Ivanović; Simone A. Del Grosso; Aritra Chowdhury; Andrea Sottini; Daniel Nettels; Robert B. Best; Benjamin Schuler (Proceedings of the National Academy of Sciences, 2025)
Biomolecular condensates form by phase separation of biological polymers and have important functions in the cell—functions that are inherently linked to their physical properties at different scales. A notable aspect of such membraneless organelles is that their viscoelastic properties can vary by orders of magnitude, but it has remained unclear how these pronounced differences are rooted in the nanoscale dynamics at the molecular level. Here, we investigate a series of condensates formed by complex coacervation of highly charged disordered proteins and polypeptides that span about two orders of magnitude in bulk viscosity. We find that their viscosity is highly correlated with protein translational diffusion and nano- to microsecond chain dynamics. Remarkably, analytical relations from polymer physics can predict condensate viscosity from diffusivity and chain dynamics, and vice versa, even for more hydrophobic disordered proteins and for synthetic polyelectrolytes, indicating a mechanistic link across several decades of length- and timescales. Atomistic simulations reveal that the observed differences in friction—a key quantity underlying these relations—reflect differences in interresidue contact lifetimes as a function of arginine content and salt concentration, leading to the vastly different dynamics among condensates. The rapid exchange of interresidue contacts we observe may be a general mechanism for preventing dynamic arrest in compartments densely packed with polyelectrolytes, such as the cell nucleus.